Respuesta :

QUESTION 1

The given circle has equation:

[tex]x^2+y^2=16[/tex]

We can rewrite to obtain;

[tex](x-0)^2+(y-0)^2=4^2[/tex]

This is equation is now in the form;

[tex](x-h)^2+(y-k)^2=r^2[/tex]

Where (h,k)=(0,0) is the center of the circle and [tex]r=4[/tex] is the radius.

QUESTION 2

The center of the circle is at (1,1) and passes through the point (4,5).

The radius of this circle is given by;

[tex]r=\sqrt{(4-1)^2+(5-1)^2}[/tex]

[tex]r=\sqrt{(3)^2+(4)^2}[/tex]

[tex]r=\sqrt{9+16}[/tex]

[tex]r=\sqrt{25}[/tex]

[tex]r=5[/tex] units.

We substitute into the formula;

[tex](x-h)^2+(y-k)^2=r^2[/tex]

[tex](x-1)^2+(y-1)^2=5^2[/tex]

[tex](x-1)^2+(y-1)^2=25[/tex]

Expand if you wish;

[tex]x^2-2x+1+y^2-2y+1=25[/tex]

[tex]x^2+y^2-2x-2y+2-25=0[/tex]

[tex]x^2+y^2-2x-2y-23=0[/tex]

Ver imagen kudzordzifrancis